2(x+5)+3=5x-3(-4+x)

Simple and best practice solution for 2(x+5)+3=5x-3(-4+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+5)+3=5x-3(-4+x) equation:



2(x+5)+3=5x-3(-4+x)
We move all terms to the left:
2(x+5)+3-(5x-3(-4+x))=0
We add all the numbers together, and all the variables
2(x+5)-(5x-3(x-4))+3=0
We multiply parentheses
2x-(5x-3(x-4))+10+3=0
We calculate terms in parentheses: -(5x-3(x-4)), so:
5x-3(x-4)
We multiply parentheses
5x-3x+12
We add all the numbers together, and all the variables
2x+12
Back to the equation:
-(2x+12)
We add all the numbers together, and all the variables
2x-(2x+12)+13=0
We get rid of parentheses
2x-2x-12+13=0
We add all the numbers together, and all the variables
1!=0
There is no solution for this equation

See similar equations:

| 2(x-3)+4(x-5)=-2 | | 8x-4=6x-1 | | 6(1-2m=-7m+11 | | 29x^2-122x+90=25765 | | -3/2+1/3u=-6/7 | | 16−8x=14−7x | | 8x+7=136 | | 20j+3j-18j-3j=8 | | x/5+20=24 | | 3(x+3)=2(x+10) | | 24=6x+4x | | -y/5=51 | | 0=5r | | 16x+3=8+7x+4x | | 2x+1*2x-1=15 | | 6x+6+8x=76 | | 16x-122+20x-166=360 | | 3a-5=7a+3. | | (2+3x°)=62 | | 14x+30=100 | | 5x10=12 | | -13x+4x+360=0 | | 3m+25=52 | | 4z-6=z+9 | | 5^(2x+1=25 | | -2(n+3)+8=-2 | | B(x)=x^2-36 | | 6(3+t)=42 | | 6x=127,2 | | 8y+8y=40 | | A=13+2b | | 3/8(y)=23/4 |

Equations solver categories